2011
DOI: 10.1007/s13238-011-1097-z
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 axis modulates bone marrow mesenchymal stem cell apoptosis, migration and cytokine secretion

Abstract: Bone marrow mesenchymal stem cells (MSCs) are considered as a promising cell source to treat the acute myocardial infarction. However, over 90% of the stem cells usually die in the first three days of transplantation. Survival potential, migration ability and paracrine capacity have been considered as the most important three factors for cell transplantation in the ischemic cardiac treatment. We hypothesized that stromal-derived factor-1 (SDF-1)/CXCR4 axis plays a critical role in the regulation of these proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 42 publications
9
176
2
2
Order By: Relevance
“…Although the underlying mechanisms for the impaired survival of the ex vivo expanded patient-derived BM MSCs remain elusive, we may speculate that the observed decreased constitutive production of SDF-1 in patient MSC cultures compared with normal individuals may have a role. In favor of this hypothesis is a recent study demonstrating that SDF-1 pretreatment significantly attenuates oxidative stress-induced MSC apoptosis in rats, thereby suggesting a critical role of SDF-1 in MSC survival [38]. Notably, SDF-1 interaction with its cognate receptor CXCR4 on CLL cells has also been reported to regulate the trafficking and homing of leukemic cells in the BM, where it actively protects them from spontaneous and drug-induced apoptosis [5,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms for the impaired survival of the ex vivo expanded patient-derived BM MSCs remain elusive, we may speculate that the observed decreased constitutive production of SDF-1 in patient MSC cultures compared with normal individuals may have a role. In favor of this hypothesis is a recent study demonstrating that SDF-1 pretreatment significantly attenuates oxidative stress-induced MSC apoptosis in rats, thereby suggesting a critical role of SDF-1 in MSC survival [38]. Notably, SDF-1 interaction with its cognate receptor CXCR4 on CLL cells has also been reported to regulate the trafficking and homing of leukemic cells in the BM, where it actively protects them from spontaneous and drug-induced apoptosis [5,39].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of SDFdependent migration of MSCs involves the activation of alpha serine/ threonine-protein kinase (AKT) and extracellular-signal-regulated kinases (ERK) signalling pathways [37,38]. Inflammatory TNF-a also mediates the invasion of MSCs into the bone-healing site [39].…”
Section: Migration Of Mscsmentioning
confidence: 99%
“…In addition, SDF-1 reduces MSC apoptosis via the PI3K/Akt pathway and improves survival in hypoxic conditions. Liu et al 65 found that in vitro, MSCs incubated with SDF-1 had significantly reduced rates of apoptosis and an increased Bcl-2 to Bax ratio. Stromal-derived factor 1 treatment also improved MSC migration and release of paracrine factors, both of which are vital to their therapeutic efficacy.…”
Section: Survivalmentioning
confidence: 99%
“…Higher SDF-1 expression in turn leads to recruitment and increased survival of MSCs in the injured regions of myocardium via the activation of PI3K/ Akt. 65,100 Stromal-derived factor 1 has a complementary 7-transmembrane G-coupled receptor, CXCR4 (expressed by MSCs and CSCs), which is required for their migratory process. 101,102 To test the efficacy of the SDF-1 on the migratory pattern of stem cells, one group inhibited binding of this ligand to the CXCR4 receptor with AMD3100.…”
mentioning
confidence: 99%